Great tits growing old: selective disappearance and the partitioning of senescence to stages within the breeding cycle. - Bouwhuis, S; Sheldon, B; Verhulst, S; Charmantier, A (2009)
Deterioration of reproductive traits with age is observed in an increasing number of species. Although such deterioration is often attributed to reproductive senescence, a within-individual decline in reproductive success with age, few studies on wild animals have focused on direct fitness measures while accounting for selective disappearance and terminal effects, and to our knowledge none have determined how senescence effects arise from underlying reproductive traits. We show for female great tits that such an approach helps understanding of the onset, impact and architecture of senescence. Cross-sectional analysis of 49 years of breeding data shows annual recruit production to decline from 3.5 years of age, this decline affecting 9 per cent of females each year. Longitudinal analyses, however, show that selective disappearance of poor-quality breeders partly masks senescence, which in fact starts at 2.8 years and affects 21 per cent of females each year. There is no evidence for abrupt terminal effects. Analyses of underlying traits show no deterioration in clutch size, but significant declines in brood size and fledgling number. Furthermore, these traits contribute -9, 12 and 39 per cent to the senescent decline in recruit production, respectively. Besides providing detailed knowledge of the patterns and architecture of senescence in a natural population, these results illustrate the importance of modelling individual variation, and facilitate study of the underlying mechanisms of senescence.